Proteome Analysis of USP7 Substrates Revealed Its Role in Melanoma Through PI3K/Akt/FOXO and AMPK Pathways - Gao, Lanyang; Zhu, Danli; Wang, Qin; Bao, Zheng; Yin, Shigang; Qiang, Huiyan; Wieland, Heinrich; Zhang, Jinyue; Teichmann, Alexander; Jia, Jing (Frontiers in Oncology, 2021)
The ubiquitin-specific protease 7 (USP7) , as a deubiquitinating enzyme, paly an important role in tumor progression by various mechanisms and serves as a potential therapeutic target. However, the functional role of USP7 in melanoma remains elusive. Here, we found that USP7 is overexpressed in human melanoma by tissue microarray. We performed TMT-based quantitative proteomic analysis to evaluate the A375 human melanoma cells treated with siRNA of USP7. Our data revealed specific proteins as well as multiple pathways and processes that are impacted by USP7. We found that the phosphatidylinositol-3-kinases/Akt (PI3K-Akt), forkhead box O (FOXO), and AMP-activated protein kinase (AMPK) signaling pathways may be closely related to USP7 expression in melanoma. Moreover, knockdown of USP7 in A375 cells, particularly USP7 knockout using CRISPR-Cas9, verified that USP7 regulates cell proliferation in vivo and in vitro. The results showed that inhibition of USP7 increases expression of the AMPK beta (PRKAB1), caspase 7(CASP7), and protein phosphatase 2 subunit B R3 isoform (PPP2R3A), while attenuating expression of C subunit of vacuolar ATPase (ATP6V0C), and peroxisomal biogenesis factor 11 beta (PEX11B). In summary, These findings reveal an important role of USP7 in regulating melanoma progression via PI3K/Akt/FOXO and AMPK signaling pathways , and implicate USP7 as an attractive anticancer target for melanoma.